Urgensi Kepemimpinan Multidimensi Gembala dalam Era Digital - Joni Manumpak Parulian Gultom (Sekolah Tinggi Teologi Jaffray Jakarta, 2022)
Multi dimension shepherd leadership is urgent in the digital age. They move with this model in their vision and insight into the socio-cultural transformation of ordinary people to digital. Shepherd is experiencing mental and emotional health problems. They choose to withdraw from church services because of fatigue, loneliness, and mental disorders. The question what is the meaning of multi-dimension pastoral leadership? What form of multi-dimension leadership is needed? And what strategies can be developed? The purpose of the research is to explain the meaning of multi-dimension pastoral leadership, describe emotional intelligence as an integral part of balanced multi-dimension leadership, and describe the strategies that can be carried out in the development of multidimensional pastoral leadership. The research method used with a qualitative description explores the understanding of multi-dimension leadership in general and its current development. Then the discussion of the shepherd's emotional intelligence continued with the stages and dimensions that can be applied, the description of the multi-dimension leadership service strategy physically and virtually. The result is that multi-dimension leadership relies on the shepherd's emotional intelligence in communication, interaction, innovation, and creativity; Leadership is evolving and is greatly appreciated. Shepherds have multidimensional abilities creating breakthroughs in responding to these challenges